Smad2/3 Upregulates the Expression of Vimentin and Affects Its Distribution in DBP-Exposed Sertoli Cells - Xi Zhang; Xiaogang Wang; Taixiu Liu; Min Mo; Lin Ao; Jinyi Liu; Jia Cao; Zhihong Cui (PPAR Research)
Sertoli cells (SCs) in the testes provide physical and nutritional support to germ cells. The vimentin cytoskeleton in SCs is disrupted by dibutyl phthalate (DBP), which leads to SCs dysfunction. In a previous study, we found that peroxisome proliferator-activated receptor alpha (PPARα) influenced the distribution of vimentin by affecting its phosphorylation in DBP-exposed SCs. In the present study, we investigated the role of Smad2/3 in regulating the expression of vimentin in DBP-exposed SCs. We hypothesized that Smad2/3 affects the distribution of vimentin by regulating its expression and that there is cross talk between Smad2/3 and PPARα. The real-time PCR and ChIP-qPCR results showed that SB431542 (an inhibitor of Smad2/3) could significantly attenuate the expression of vimentin induced by DBP in SCs. Phosphorylated and soluble vimentin were both downregulated by SB431542 pretreatment. WY14643 (an agonist of PPARα) pretreatment stimulated, while GW6471 (an antagonist of PPARα) inhibited, the activity of Smad2/3; SB431542 pretreatment also inhibited the activity of PPARα, but it did not rescue the DBP-induced collapse in vimentin. Our results suggest that, in addition to promoting the phosphorylation of vimentin, DBP also stimulates the expression of vimentin by activating Smad2/3 in SCs and thereby induces irregular vimentin distribution.